A functional feature modeling method. (August 2017) - Cheng, Zhengrong; Ma, Yongsheng
Abstract: With the advances in CAD technology, it has been increasingly convenient to model product shapes digitally. For example, in a feature-based parametric CAD system, the product shape could be parameterized and thus altered with the change of parameters. However, without a consistent and systematic CAD modeling method, CAD models are not robust enough to capture functional design knowledge and cope with design changes, especially functional changes. A poorly constructed CAD model could result in erroneous or inconsistent design that requires a lot of expertise, manpower and repetitive computation to rebuild a valid and consistent model. The situation can be worse if the model is complex. The gap between functional design considerations and procedural CAD modeling demands an integrated CAD modeling approach. This paper proposes a functional feature-based CAD modeling method to guide designers building CAD models that are valid and yet agile to represent functional design considerations. A case study is presented to demonstrate the feasibility of the proposed research.